2003
DOI: 10.3402/ijch.v62i3.17560
|View full text |Cite
|
Sign up to set email alerts
|

Diet and mental health in the Arctic: is diet an important risk factor for mental health in circumpolar peoples? - a review

Abstract: Background. The people living in Arctic and Subarctic environments have adapted to cold temperatures, short growing seasons, and low precipitation, but their traditional ways are now changing due to increased contact with Western society. The rapid alteration of circumpolar cultures has led to generational changes in diet from traditional foods to the processed groceries common in modern stores. Objectives. Develop a link between changing traditional diets and mental health that may have substantial consequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 124 publications
1
40
0
Order By: Relevance
“…A few studies have reported that change in diet may be associated with quality of life. A review study by McGrath-Hanna et al [27] suggested that the change from traditional to western diet is negatively associated with mental health of circumpolar peoples. Corle et al [5] found that subjects who changed to a low-fat, highfiber, high-fruit and vegetable diet reported significantly higher domains for health belief, health action, and selfcare after 1 year than did controls.…”
Section: Discussionmentioning
confidence: 98%
“…A few studies have reported that change in diet may be associated with quality of life. A review study by McGrath-Hanna et al [27] suggested that the change from traditional to western diet is negatively associated with mental health of circumpolar peoples. Corle et al [5] found that subjects who changed to a low-fat, highfiber, high-fruit and vegetable diet reported significantly higher domains for health belief, health action, and selfcare after 1 year than did controls.…”
Section: Discussionmentioning
confidence: 98%
“…Diet is essential for maintaining general health and is particularly important for the brain, as it requires a steady supply of energy (11)(12). A number of studies on the lack of energy as a consequence of fasting consistently showed a decline in attention and cognitive functions and an increase in fatigue, headaches, and irritability (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…The rates of suicide and alcoholism are also very high in Alaska and the Arctic (12,17,19,20,21). Again, both epigenetic and potential genetic risk factors need to be identified and the lack of epidemiological studies has been a major barrier.…”
Section: Complex Disorders With a Neuroscience Componentmentioning
confidence: 99%
“…In relation to the brain, emerging evidence emphasizes the embedding of life experience and points to the lifelong impact of health experiences on the foetus and child during the important developmental stages identified as critical periods or sensitive stages (5). Neuroscience research in the Arctic needs to combine the advances in understanding the molecular mechanisms of disease with the identification of environmental and lifestyle factors that influence health (3,4,11,12,29).…”
Section: Introductionmentioning
confidence: 99%